THEORETICAL APPROACHES AND PRACTICAL STRATEGIES FOR RESILIENT DEVELOPMENT - Kravchuk, Vlad (Personality and environmental issues, 2025)
The article reveals the concept of resilience in the modern scientific literature, analyzes the main approaches to the study of the phenomenon as a person's ability to overcome life's difficulties, as resistance to stress and the ability of the psyche to recover. The historical dynamics of the development of resilience research and the potential for its use are demonstrated.In modern psychological science, an important place is occupied by the study of ideas on how to make a person happier, more competitive, adaptive and able to withstand the challenges of our time, which involve many difficulties associated with the rapid pace of development in all spheres. That is why the phenomenon of resilience is actively gaining popularity and is increasingly attracting attention as an opportunity to understand what mechanisms are needed to withstand severe stress. It is important to note that the reasons that negatively affect the human psyche are not only the rapidly developing world, but also many other factors, which encourages scientists to search for these reasons, measure them, the ability to resist, the possibility of recovery, etc.The study of the problem of resilience is not uniform in theoretical terms, because compared to the level of Western research in Europe and the United States, domestic concepts of understanding the phenomenon of resilience are lagging far behind, but the current situation in the socio-political, economic and security spheres in Ukraine requires significant attention to the use of existing tools, their adaptation and development of new ones.